PERILAKU SOSIAL MAHASISWA DALAM KEHIDUPAN DI BARAK PADA KOTA PALANGKA RAYA - Mikdar, U.Z. (Universitas Kadiri, 2019)
In the City of Palangka Raya there are types of conventional boarding houses, modification boarding houses and semi-boarding boarding houses. The problems in this study are (1) How is the social interaction of students in life in the boarding houses of Palangka Raya City; and (2) What social behavior is formed in the process of social interaction of students in life in the boarding houses of Palangka Raya City. The method used is qualitative. The results of this study are (1) The interaction of students living in conventional boarding houses and semi-boarding boarding houses shows social behavior such as help and kinship. Whereas in the modified boarding houses there are individualistic tendencies. The same thing also happens with conventional boarding houses that are not present and / or far from their owners, the residents tend to be relatively more free; (2) The learning pattern of students living in conventional boarding houses and modification boarding houses tends to be only when they want to take exams and have assignments. While in the semi boarding boarding houses, in addition to studying at the campus also learn in the boarding houses (special places) that have been provided by the boarding houses owner. In addition, the salient social reality, the erosion of social values in the life of